2015
DOI: 10.1007/s00216-015-8669-3
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of fluorene fluorescence by single-walled carbon nanotube dispersions with surfactants: application for fluorene quantification in wastewater

Abstract: The fluorescence of fluorene in aqueous solutions of surfactants of different natures, anionic sodium dodecylsulphate (SDS), cationic cetyltrimethyl ammonium chloride (CTAC) and non-ionic polyoxyethylene-23-lauryl ether (Brij 35), as well as in single-walled carbon nanotube (SWCNT) dispersions in these surfactants, has been studied and compared. A fluorescence quenching phenomenon has been observed in the presence of SWCNT, the effect being stronger for dispersions in CTAC, related to the improved dispersion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(66 reference statements)
2
10
1
Order By: Relevance
“…This quenching effect is stronger for the anionic surfactant, likely due to the larger space between the head ionic groups of SDS micelles compared to those of CTAB or DTAB, which makes the penetration of the riboflavin molecule into the micelles easier [ 32 ]. These results significantly differ from those found for the fluorescence of other aromatic molecules like fluorene in the presence of surfactant solutions [ 44 ], where the fluorescence intensity increased in the presence of Brij L23 or CTAB, ascribed to a solubilization effect of fluorene. On the other hand, the comparison of the results obtained for the cationic surfactants CTAB and DTAB, which have identical structure and only differ in the chain length (16 and 12 carbon atoms, respectively) indicates that both have the same effect on the fluorescence of riboflavin.…”
Section: Resultscontrasting
confidence: 98%
“…This quenching effect is stronger for the anionic surfactant, likely due to the larger space between the head ionic groups of SDS micelles compared to those of CTAB or DTAB, which makes the penetration of the riboflavin molecule into the micelles easier [ 32 ]. These results significantly differ from those found for the fluorescence of other aromatic molecules like fluorene in the presence of surfactant solutions [ 44 ], where the fluorescence intensity increased in the presence of Brij L23 or CTAB, ascribed to a solubilization effect of fluorene. On the other hand, the comparison of the results obtained for the cationic surfactants CTAB and DTAB, which have identical structure and only differ in the chain length (16 and 12 carbon atoms, respectively) indicates that both have the same effect on the fluorescence of riboflavin.…”
Section: Resultscontrasting
confidence: 98%
“…Experimental results confirm that the magnitude of the quenching effect depends strongly on the nature of the surfactant and only slightly on its chain length, hence on the size of the micelles, and that the cationic surfactants are the most suitable for exfoliating G in aqueous solutions. This is consistent with the results from the previous study [ 24 ], which demonstrated that G dispersions in the cationic surfactants were the most efficient in decreasing the fluorescence intensity of riboflavin. Further, it is also in good agreement with former works [ 25 ] that proved that non-ionic surfactants are less efficient than ionic ones in dispersing G, which suggests that strong G-surfactant interactions are needed to achieve a good G exfoliation, as well as stable and homogenous aqueous dispersions.…”
Section: Resultssupporting
confidence: 93%
“…Unexpectedly, for dispersions in this surfactant, the three G percentages that were studied exerted the same effect on the fluorescence of riboflavin, whereas for dispersions in CTAB, the greater the amount of G, the more pronounced the quenching effect. This unexpected behaviour was explained [ 24 ] when considering that a greater number of DTAB monomers with shorter chain than CTAB can adsorb onto the G flakes. In addition, taking into account that the CMC of DTAB is 15.5 times larger than the CMC of CTAB, the concentration of monomers in the former dispersions is higher, hence resulting in a stronger quenching effect.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This assay offers an advantage over other common viability assays because it is readily adapted to evaluate viability of cells grown in three dimensional cultures. Although it is known that CNTs can quench luminesence(Palencia et al, 2015), prior to our studies, it was unknown what impact MWCNTs had on the accuracy of CellTiter-Glo® luminescence measurements. We show that an additional centrifugation step after cell lysis is sufficient to remove MWCNT interference from the assay.…”
Section: Discussionmentioning
confidence: 99%